"It seemed like a punishment": Teacher transfers, hollow nationalism, and the intimate state in Eritrea. (November 2013) - RIGGAN, JENNIFER
ABSTRACT: Discourses of the punishing state that circulated in Eritrea at a time when the government had become increasingly coercive were articulated especially clearly in debates over teacher transfers. Teachers imagined the state on the basis of their intimate encounters with its bureaucrats, who were thought of as capable of punishing, manipulating, or being manipulated. In a country once noted for the effervescent, revolutionary celebration of the state's capacity to defend and develop the nation, thinking of the state as pernicious challenged the core tenets of Eritrean nationalism but left intact lingering fantasies of state fairness. By examining the complexity of debates about teacher transfers, I uncover a multifaceted commentary on government power, a dialogue over the nature and meaning of the notion of duty to the nation, and a reworked popular imaginary of the state.